DETERMINATION OF WORK ACHIEVEMENT AND PRODUCTIVITY: ANALYSIS OF COMMITMENT AND WORK DISCIPLINE (HR LITERATURE REVIEW) - Mustakiem, Sirta (Dinasti Publisher, 2022)
This study is intended to determine the effect of commitment and work discipline on work performance and productivity. This research is a case study to see that commitment and work discipline are important factors in employee productivity in providing services to participants. The interaction between participants and the presence of a high workload is believed to have an effect on work performance. Therefore, work performance needs to be owned by employees because it is related to employee work productivity. The purpose of writing this article is to build hypotheses that are useful for further research. This article reviews the variables that affect work performance and productivity. The result of this literature review is that commitment and work discipline factors affect work performance and employee productivity.